Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1177/004051757804800903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Construction and Weave on Some Mechanical Properties of Untreated and Resin-Treated Cotton Fabrics

Abstract: The analysis of sets of fabrics of different woven constructions made from the same count of yarn indicates that the differences in mechanical properties arise mainly from weave differences. Increase in flex abrasion is compensated by a de crease in'tear strength and vice versa. Analysis reveals that the initial properties of the twill weave are more balanced for higher levels of crease recoveries than those of the other fabrics. Twill-weave fabrics show high tensile strength. While basket-weave fabrics give h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Fabric abrasion resistance was reported to be higher for longer polyester and combed cotton fibers compared to shorter polyester and carded cotton fibers (Bhortakke, Nishimura, & Matsuo, 1997). The analysis of sets of fabrics of different woven constructions indicated that differences in abrasion resistance arise mainly from weave differences (Mehta et al, 1978;Ruppenicker, Sawhney, Calamari, & Harper, 1997). The plain weave fabrics were best suited for high flex abrasion resistance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fabric abrasion resistance was reported to be higher for longer polyester and combed cotton fibers compared to shorter polyester and carded cotton fibers (Bhortakke, Nishimura, & Matsuo, 1997). The analysis of sets of fabrics of different woven constructions indicated that differences in abrasion resistance arise mainly from weave differences (Mehta et al, 1978;Ruppenicker, Sawhney, Calamari, & Harper, 1997). The plain weave fabrics were best suited for high flex abrasion resistance.…”
Section: Introductionmentioning
confidence: 98%
“…The plain weave fabrics were best suited for high flex abrasion resistance. Twill and sateen fabrics had lower flex abrasion resistance than the corresponding plain fabrics (Mehta et al, 1978). Akgun et al reported that compact fabric structures with high yarn crossing numbers (yarn intersections) were more resistant to the effects of abrasion.…”
Section: Introductionmentioning
confidence: 99%
“…It can be said, therefore, that the warp yarns contribute to the longitudinal properties of a woven textile, and the weft yarns contribute to the transverse properties [36]. In some woven structures, particularly nontechnical textiles, the warp yarns typically have a higher tensile strength than weft yarns [37] and this relates to the degree of crimp present in the yarns after weaving. During the weaving process, warp yarns are held under tension and weft yarns are passed under and over at 90 • .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of sets of fabrics of different woven constructions made from the same count of yarn indicates that the differences in mechanical properties arise mainly from the weave differences. The plain-weave fabrics are best suited for high flex abrasion resistance [11].…”
mentioning
confidence: 99%